Yolk Sac Tumor in an Eight-Year-Old Girl: A Case Report and Literature Review - Chen, Li Hsun; Yip, Kui-Chuen; Wu, Hsing-Ju; Yong, Su-Boon (Frontiers in Pediatrics, 2019)
Yolk sac tumor (YST), which most frequently arises in the gonads as a type of germ cell tumor, is rare in children but is highly malignant. It has been suggested that alpha-fetoprotein (AFP) can be applied as a feasible tumor marker because its level was elevated in > 90% of YST. The treatment generally involves debulking surgery of tumors followed by systemic chemotherapy. Metastasis process of YST in children is different from that in adults and thus the treatment option is required. In this study, we described a rare case of YST in terms of the clinical manifestation, imaging and histopathology findings, diagnosis and treatment in an eight-year-old girl. Furthermore, it is important to investigate more thoroughly a patient with history of intermittent abdominal pain and fever with previously multiple accesses, because these might be the critical signs for YST that should be alarmed for early treatment. Although YST is rare in children, pediatric physicians should be aware of this and prompt treatment should be addressed.